PERSPEKTIF SISWA DAN GURU TERHADAP MEDIA DIGITAL DAN KONVESIONAL DALAM PEMBELAJARAN BAHASA INDONESIA - Riskiawati , Hila Lisa; Islam , Raudhatul; Shobah, Syukron Malikus (Universitas Islam Zainul Hasan Genggong, 2025)
The purpose of this study is that researchers want to know the perspectives of digital media and conventional media in Indonesian language learning at Bhakti Pertiwi Junior High School. The formulation of the problem in this study is how the perspectives of students and teachers on digital media and conventional media in Indonesian language learning. Digital media is a learning media that uses technology as a learning tool, such as the internet and various other devices. Conventional media is a traditional media known as lecture learning, this method has been used since long ago as a medium of communication orally and in writing between teachers and students. The method used in this research is to use descriptive qualitative research. The subject of this research is Bhakti Pertiwi Junior High School. The object of this research is students' and teachers' perspectives on digital and conventional media. The data sources used are books, articles, and journals. Data collection techniques are listening, recording, and taking notes. The data analysis technique used in this research is by categorizing the data, describing it in units of analysis, and making conclusions. The results found in this study according to digital and conventional learning media teachers have a role, namely as a tool in the learning process. The goal is that students at Bhakti Pertiwi Junior High School quickly understand and understand the material conveyed by a teacher. In addition, the purpose of using both digital and conventional media is so that students are not bored with the learning that is done, for example, if a teacher often uses conventional media, students may become bored, bored, and want to play games on digital media.